Effects of Frisol F, Promot and Fluorescent Pseudomonads Against Fusarium Wilt of Melon Caused by Fusarium oxysporum f.sp. melonis Race 1,2 in Controlled Conditions - Salih Maden; Kudret Erzurum (Journal of Agricultural Sciences)
The organic material, Frisol F, was incorporated to the potting soil at the rate of 1,13 g/kg soil. Application of this material alone or in combination with antagonistic microorganisms did not reduce wilt development. The commercial preparation of Trichoderma koningli and T. harzianum, Promot 1 g/kg soil reduced wilt incidence 42.86 % but this was not statistically different than the control. When melon seeds were soaked in the suspensions of Pseudomonas fluorescens and P. putida of 109cell/ml for 2 hours wilt incidence was reduced 54.14 and 71.43 % respectively, the latter being significant.